New approaches to training specialists of preschool education in the transition to distance learning - Nadiia Lazarovych (Vasyl Stefanyk Precarpathian National University, 2017)
The paper analyzes the features of professional training of pre-school education indistance learning. The efficiency of the use of a mixed form of education for students of "earlychildhood education". Describes the main conditions for successful use ofdistance learningfor the training of future teachers. Key words: information space, distance learning, information technology (IT), earlychildhood education, personal and psychological characteristics, educational features